Reconfigurable anomalous reflectors with stretchable elastic substrates at 140 GHz band - Kato Yuto; Yonemura Kazuma; Seki Kento; Kambara Retsuku; Sanada Atsushi (Nanophotonics)
We propose reconfigurable anomalous reflectors with stretchable elastic substrates. The proposed reflector dynamically controls the reflection direction by mechanically stretching the substrate to induce a physical change of the unit cell period. Owing to the simple and scalable tuning mechanism, the proposed approach is applicable in the millimeter-wave and terahertz bands for a wide reflection steering. To demonstrate the proposed approach, stretchable anomalous reflectors are designed at 140 GHz for normal incident waves. From full-wave simulations, we numerically confirm that highly efficient anomalous reflections with suppressed parasitic reflections in the undesired directions are achieved toward shallower angles as the substrate is stretched. We experimentally demonstrate that the proposed reflectors allow a dynamic control of the reflection direction with wide steering ranges of more than 20°. Moreover, we confirm that the measured efficiencies of the anomalous reflections hardly deteriorate when stretching and maintain practically acceptable performances of over 50 %. The proposed stretchable reflectors have a potential to be used for a reconfigurable intelligent surface (RIS) that realizes dynamic optimizations of the wireless environment in the 6G communication.